Modeling the impact of combined vaccination programs against varicella and herpes zoster in Norway. Issue 8 (14th February 2018) - Marchetti, Sabina; Guzzetta, Giorgio; Flem, Elmira; Mirinaviciute, Grazina; Scalia Tomba, Gianpaolo; Manfredi, Piero
Highlights: Adoption of varicella vaccination in Europe is limited due to its unclear effects on herpes zoster. New perspectives of HZ control are offered by new subunit recombinant zoster vaccine. We used mathematical modeling to investigate a complete range of vaccination strategies. Given uncertainty on boosting, targeted vaccination of adolescents is a viable strategy. Abstract: Background: Adoption of varicella immunization in Europe is limited due to a predicted increase in the incidence of herpes zoster (HZ) resulting from a removal of exogenous boosting by varicella vaccination. Most available assessments of immunization strategies only considered universal varicella vaccination (alone or in combination with HZ by the live vaccine). The development of a new subunit recombinant zoster vaccine may provide new perspectives of HZ control. Methods: We used a mathematical model for VZV in Norway based on the progressive immunity formulation of exogenous boosting. We evaluated a complete range of alternative immunization options against varicella and HZ including both universal and targeted varicella vaccination, either alone or with zoster immunization, and zoster immunization alone. We considered all values of the boosting intensity consistent with the Norwegian HZ incidence and compared the performance of the currently available live vaccine vs. a new recombinant vaccine. Results: Universal varicella vaccination alone resulted in a marked increase in the incidence of HZ under all scenarios considered. Even under the most favorable hypotheses on the magnitude of the boosting intensity, this increase could be mitigated only by a parallel HZ immunization with a recombinant vaccine, assuming a long duration of protection. Targeted varicella immunization of adolescents resulted in a modest increase in the HZ incidence which could be counterbalanced by both the live and, especially, the recombinant vaccine. Conclusions: Given current knowledge on HZ pathogenesis and exogenous boosting, targeted varicella vaccination of adolescents was the only strategy that was not predicted to impact the epidemiology of HZ, and therefore it may represent a suitable alternative to universal vaccination. These results are aimed to support vaccine policy decisions in Norway and other countries with a similar VZV epidemiology.